Pro-inflammatory role of NLRP3 inflammasome in experimental sterile corneal inflammation - Shimizu, Hiroaki (Sci Rep, 2019)
We evaluated the role of NLR family pyrin domain containing 3 (NLRP3) inflammasome in sterile corneal inflammation caused by lipopolysaccharide (LPS) or alkali burns in C57BL6 mice or NLRP3 KO (Nlrp3(−/−)) mice. Various molecules related to the NLRP3 inflammasome were upregulated in C57BL6 mice after both alkali burn injury and LPS treatment. After alkali burn injury, the corneal opacity grade was significantly reduced in Nlrp3(−/−) mice compared with C57BL6 mice. In Nlrp3(−/−) mice, Gr-1 immunoreactivity and MMP-9 mRNA expression in the corneal stroma were significantly reduced by both LPS treatment and alkali burn injury. Quantitative PCR and immunohistochemistry revealed that IL-1β and MMP-9 expression in the corneal stroma were down-regulated in Nlrp3(−/−) mice with both alkali burn injury and LPS treatment. These findings suggest that the NLRP3 inflammasome has a pro-inflammatory effect in the cornea by recruiting neutrophils to sites of inflammation.